Clustering Graf dengan Algoritma Rantai Markov - Theophilus Wellem; Yessica Nataliani (Fakultas Teknologi Informasi Universitas Kristen Satya Wacana, 2017)
Graph clustering is the task of grouping the vertices of the graph into clusters taking into consideration the edge structure of the graph in such a way that there should be many edges within each cluster and relatively few between the clusters. The objective of this paper is to apply Markov clustering algorithm. Two examples are used to demonstrate the algorithm. In the first example, simple graph is presented to illustrate the computation of this algorithm. While the second example is to study the hosts’ interaction behavior using graph clustering algorithm. The Markov clustering algorithm is used to group (cluster) hosts which have interaction using the HTTP protocol. Using real network traces, the clustering results show that the algorithm successfully group the hosts to their corresponding clusters.